1996
DOI: 10.1111/j.1365-2958.1996.tb02645.x
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic SycE and SycH chaperones of Yersinia protect the region of YopE and YopH involved in translocation across eukaryotic cell membranes

Abstract: Yersinia adhering at the surface of eukaryotic cells secrete a set of proteins called Yops. This secretion which occurs via a type III secretion pathway is immediately followed by the injection of some Yops into the cytosol of eukaryotic cells. Translocation of YopE and YopH across the eukaryotic cell membranes requires the presence of the translocators YopB and YopD. YopE and YopH are modular proteins composed of an N-terminal secretion signal, an internalization domain, and an effector domain. Secretion of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
209
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(215 citation statements)
references
References 73 publications
5
209
1
Order By: Relevance
“…In contrast, no cytosolic delivery of these hybrid YopE proteins was observed in the absence of recombinant, plasmid-borne SycE. SycE is a small homodimeric protein that interacts with YopE in the Yersinia cytoplasm (53), and this interaction is absolutely required for YopE translocation (14), whereas YopE secretion is not affected. Obviously, SycE serves a similar essential purpose when expressed in Salmonella.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, no cytosolic delivery of these hybrid YopE proteins was observed in the absence of recombinant, plasmid-borne SycE. SycE is a small homodimeric protein that interacts with YopE in the Yersinia cytoplasm (53), and this interaction is absolutely required for YopE translocation (14), whereas YopE secretion is not affected. Obviously, SycE serves a similar essential purpose when expressed in Salmonella.…”
Section: Discussionmentioning
confidence: 89%
“…However, knockout mutations in sycE, encoding a small cytoplasmic protein that binds as a homodimer to YopE residues 15-100, abolish secretion of mutant YopE proteins (Cheng et al 1997;Lee et al 1998). Cytoplasmic binding proteins similar to SycE have been reported for YopB, YopD, YopH, YopN, and YopT (Wattiau and Cornelis 1993;Wattiau et al 1994;Woestyn et al 1996;Day and Plano 1998;Iriarte and Cornelis 1998;Jackson et al 1998). These results led to the proposal that YopE may be initiated into the type III pathway in one of two ways, requiring an mRNA signal or binding of SycE to unfolded YopE (Fig.…”
Section: Substrate Recognitionmentioning
confidence: 99%
“…Export of these structural components is strongly facilitated by cytosolic substrate-specific chaperones, which bind respectively to the C-terminal amphipathic domains of their substrates FlgK and FlgL (chaperone FlgN), FliD (FliT), and FliC (FliS) (6)(7)(8). Although primary sequence identity is low or inapparent between the chaperones of the flagellar and virulence type III export systems, most are small, homodimeric proteins with a predicted C-terminal amphipathic helix (6,9,10), and it is suggested that they act as ''bodyguards'' to maintain monomers in an export-competent form and prevent their interaction before export (6,(10)(11)(12)(13). In the flagellar chaperones FlgN and FliT and the virulence chaperone CesT, the C-terminal region has been shown to mediate substrate binding, whereas the N terminus is responsible for homodimerization (7,14).…”
mentioning
confidence: 99%